Mission manifest: American evangelicals and Iran in the twentieth century - Shannon, Matthew K. (The United States in the world, 2024)
"This book is about Presbyterian missionaries, other Americans with ideals, and their Iranian partners during the twentieth century. It analyzes the various ways in which their respective missions became manifest in Iran, particularly the national capital of Tehran, during the reign of the last Pahlavi shah"--